Potency Of Bacteriocin For Animal Health And Food Safety - Siti Chotiah (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
The emergence of antibiotic resistance in many bacteria related to animal and public health stresses the importance of decreasing the use of antibiotics in animal production. The reduction of antibiotic application in livestock can only be achieved if alternative antimicrobial strategies are available. A number of strategies have been explored to control microbial pathogens and to improve growth and feed efficiency in livestock without the use of antibiotics. Bacteriocins have been more extensively studied and proposed as potential alternatives to conventional antibiotics in animal husbandry. Bacteriocins are antimicrobial peptides ribosomally synthesized by many species of Bacteria and some strains of Archaea. In general, bacteriocins just exhibited bactericidal or bacteriostatic activity against other bacteria that are closely related to the producing strain. The main mechanisms of bacteriocin activity vary from pore formation in cytoplasmic membranes to the inhibition of cell wall biosynthesis and enzyme activities (RNAse or DNAse) in target cells. The use of bacteriocins in probiotic applications, as preservatives, and most excitingly as alternatives to conventional antibiotics is being broadly explored and studied. This review will describe the bacteriocins potency for animal health and food safety, as well as the results of bacteriocin study that had been conducted in Indonesia.Key words: Bacteriocin, animal health, food safety